Effect Of Career Path On Organizational Sustainability Through Innovative Work Behavior - Gustiah, Indira Puspa; Saluy, Ahmad Badawy; Kasmir, Kasmir; Nawangsari , Lenny C (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2024)
ABSTRACT Purpose: This study aims to determine and analyze the effect of Career Path on organizational sustainability mediated by innovative work behaviorin heavy equipment companies in Indonesia. Methodology/approach: The method used in this research is descriptive quantitative method. The population in this study are all employees who work in heavy equipment companies in Indonesia. With the structural equation modeling (SEM) analysis model, 110 samples were taken. The analysis technique in this study is Partial Least Square (PLS) using the smartPLS 3.0 program to test the hypothesis. Findings: The results showed that there was a positive and significant effect of Career Path on innovative work behaviorand organizational sustainability. There is an effect of innovative work behavioron organizational sustainability. Innovative Wok Behavior can mediate the effect between Career Path and organizational sustainability in heavy equipment companies in Indonesia. Novelty/value: Innovative Wok Behavior sangat penting untuk ditingkatkan agar organizational sustainability lebih meningkat melalui upaya penerapan Career Path.